FAKTOR-FAKTOR YANG MEMPENGARUHI PRAKTIK PERATAAN LABA - Fabian Asri, 0935030513 Roni; Badjuri, Achmad (Students Journal of Accounting and Banking, 2012)
The goal of this research is to examine the influence of company factors toward income smoothing practice among listed companies at Indonesian stock exchange during 2008-2010. The factors being examined are company size, financial leverage, institution ownership, and profitability. The population in this research uses 204 manufacturing company listed in Indonesian stock exchange during 2008-2010. The sample also uses a purposive sampling technique. The data analysis for this research is using spss 17,0 for windows. Eckel index is used to spesificate income smoothing practice.The result of this research shows that size of company has significant influence to income smoothing practice. But, financial leverage, institutional ownership and profitability variables do not have significant influence to income smoothing practice.Keywords: company size, financial leverage, institution ownership, profitability and income smoothing practice.